Pioneers in cell biology [ - Cregan, Elizabeth R. (Life science readers, 2008)
Anton van Leeuwenhoek was not educated in science, but he created the best microscopes of the 17th century. He made more than 400 microscopes and used them to study living organisms. British scientist Robert Hooke was the first scientist to observe cells and give them their name. Many scientists are still making discoveries in the areas of genetics and stem cell research